2021
DOI: 10.25299/sportarea.2021.vol6(2).6347
|View full text |Cite
|
Sign up to set email alerts
|

The role of family and social media in athlete social interactions

Abstract: Social interaction is an inseparable part of human life, including an athlete, because literally, humans are social creatures. Social interactions carried out in society can be influenced by other factors such as family and social media. This study aims to determine how many roles out social media both on the social interaction of athletes. This research is quantitative research with the instrument used is a questionnaire. The population in this study was 70 National athletes from Riau Province. The analysis t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Previous research has revealed the positive impact of physical exercise on social interactions, increased self-confidence, and support for pro-social behaviour (Di Bartolomeo & Papa, 2019). Conversely, other studies have considered how family and social media influence athletes and exercise-active individuals in terms of their activities, social interactions, and communication (Gusdernawati & Widiyanto, 2021). However, after looking at Ambon City, Indonesia, there is a knowledge gap that demands urgent filling.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has revealed the positive impact of physical exercise on social interactions, increased self-confidence, and support for pro-social behaviour (Di Bartolomeo & Papa, 2019). Conversely, other studies have considered how family and social media influence athletes and exercise-active individuals in terms of their activities, social interactions, and communication (Gusdernawati & Widiyanto, 2021). However, after looking at Ambon City, Indonesia, there is a knowledge gap that demands urgent filling.…”
Section: Introductionmentioning
confidence: 99%